Design and Build an Automatic Soil Spraying Device on Soil Moisture Using Soil Moisture Sensors - Abdul Rachman Manga'; Dewi Widyawati; Fahmi; Samsul (Program Studi Teknik Komputer, 2024)
The conventional manual watering method employed by cultivators often results in uneven watering and inconsistent water levels during each irrigation session. To address this problem, automatic watering tools are commonly adopted that utilize soil moisture sensors for efficient watering. However, challenges arise in dealing with diverse soil conditions across multiple planting media. In response to these challenges, the author proposed the design and development of a soil moisture-based watering device utilizing NodeMCU ESP32 as a microcontroller connected to six soil moisture sensors. This tool aims to provide a solution for watering six different soil media with varying conditions. The system incorporates six solenoid valves to control water channels, with a relay regulating the valve performance. The testing and implementation involve watering each soil medium when the sensor detects humidity levels exceeding 2047 bits. The preliminary tests demonstrated successful operation, particularly with solenoid valve 1 exhibiting consistent performance across ten trials, leading to positive outcomes for all six solenoid valves. Overall, the proposed tool proved effective in watering different soil media, with successful results in eight out of ten trials.